Cardiovascular Protective Effects of Plant Polysaccharides: A Review - Dong, Xinli; Zhou, Mengze; Li, Yehong; Li, Yuxin; Ji, Hui; Hu, Qinghua (Frontiers in Pharmacology, 2021)
Cardiovascular disease is a kind of heart, brain, and blood vessel injury disease by the interaction of various pathological factors. The pathogenesis of cardiovascular disease is complex with various risk factors, including abnormally elevated blood pressure, glucose, and lipid metabolism disorders, atherosclerosis, thrombosis, etc. Plant polysaccharides are a special class of natural products derived from plant resources, which have the characteristics of wide sources, diverse biological activities, and low toxicity or side effects. Many studies have shown that plant polysaccharides improve cardiovascular diseases through various mechanisms such as anti-oxidative stress, restoring the metabolism of biological macromolecules, regulating the apoptosis cascade to reduce cell apoptosis, and inhibiting inflammatory signal pathways to alleviate inflammation. This article reviews the pharmacological effects and protective mechanisms of some plant polysaccharides in modulating the cardiovascular system, which is beneficial for developing more effective drugs with low side effects for management of cardiovascular diseases.